2009
DOI: 10.1159/000210082
|View full text |Cite
|
Sign up to set email alerts
|

Coronary Calcium Score in Renal Transplant Recipients

Abstract: Background: Coronary calcium score (CCS) is established as an index for the risk of coronary heart disease (CHD). The aim of this prospective study was to assess changes in CCS in patients 1 year after kidney transplantation (KTx). Method: A total of 221 consecutive renal transplant recipients were enrolled in our prospective study (140 males/81 females). CCS was analyzed by spiral multidetector CT at baseline and 1 year after KTx. Bone mineral density (BMD) was measured in the lumbar spine (L-BMD) and femur (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(2 citation statements)
references
References 56 publications
1
1
0
Order By: Relevance
“…As previously mentioned, VCs not infrequently tend to progress after KTx, even though at a lower rate as compared with dialysis patients [21, 22, 40, 41]. Some of our preliminary results, produced as yet only in abstract form [23], suggested that aortic calcifications, evaluated according to Kauppila et al [42], increased in 30% of patients over the first year after KTx.…”
Section: Clinical Consequences Of Hc In Ktxsupporting
confidence: 50%
“…As previously mentioned, VCs not infrequently tend to progress after KTx, even though at a lower rate as compared with dialysis patients [21, 22, 40, 41]. Some of our preliminary results, produced as yet only in abstract form [23], suggested that aortic calcifications, evaluated according to Kauppila et al [42], increased in 30% of patients over the first year after KTx.…”
Section: Clinical Consequences Of Hc In Ktxsupporting
confidence: 50%
“…Studies of SNF472, sotatercept, and oral activated charcoal each reported attenuation of VC progression, whereas studies of exercise training, spironolactone, and nicotinamide did not. We did not include in our review other studies which reported effects on VC after changes in kidney replacement therapies, such as several observational studies assessing the effect of kidney transplantation on VC 120 125 and several evaluating changes in VC after commencement of more frequent or longer hours of hemodialysis (such as nocturnal dialysis) 123 , 126 , 127 . These studies have predominantly reported that VC progression is attenuated by both kidney transplantation and nocturnal hemodialysis when compared with continuation of conventional hemodialysis, but not all studies have consistently shown this 119 , 124 , 125 …”
Section: Discussionmentioning
confidence: 99%